Status of threaten fish species in Narsunda river - Arefin, Fahimul; Moniruzzaman, Md; Lupa, Saymuna Tarin; Rahman, Md Ashikur; Islam, Ariful; Akter, Shirin (Research in Agriculture Livestock and Fisheries, 2018)
To identify the threatened fish species and focus on fish biodiversity conservation in the Narsunda River Kishoreganj Sadar, Kishoreganj district, the present study was conducted for a time period of 6 months (April-November, 2012). A total of 23 threatened fish species were identified in the river among them, 9 vulnerable, 11 endangered and 3 critically endangered species as well as 8 exotic fish species were also found in the River. The fishing gears used by the fishermen in Narsunda River includes 4 types of nets, 3 types of traps, 3 hooks and lines and 2 types of wounding gears whereas major fishing craft and gears were mainly wooden boat and seine net (locally called ‘ber jal’) respectively. Due to environmental degradation and manmade causes the biodiversity of this river decreasing day by day and it could be minimized by proper management and conservation techniques. Res. Agric., Livest. Fish.5(2): 259-268, August 2018